Telmisartan Modulates the Oral Mucositis Induced by 5-Fluorouracil in Hamsters - Barbosa, Maisie M.; de Araújo, Aurigena A.; de Araújo Júnior, Raimundo F.; Guerra, Gerlane C. B.; de Castro Brito, Gerly A.; Leitão, Renata C.; Ribeiro, Susana B.; de Aragão Tavares, Emanuella; Vasconcelos, Roseane C.; Garcia, Vinícius B.; de Medeiros, Caroline A. C. X. (Frontiers in Physiology, 2018)
Oral mucositis (OM) is a common adverse effect resulting from cancer therapy. The OM it has implications that may compromise oncologic treatment and decrease the patient's quality of life. The therapeutic options to prevent or treat the symptoms of OM are scarce; there is no effective therapy that improves the symptoms. Based on the need for further research for the treatment of OM, the present study objective was to evaluate the effect of telmisartan (TELM) on the oral mucositis induced by 5-fluorouracil (5-FU), using as animal model Golden Syrian hamsters. 5-FU followed by mechanical trauma (MT) on day 4 was used to induce OM in hamsters. Euthanasia occurred on the day 10. The experiments were constituted by the groups saline, mechanical trauma, 5-FU and TELM in three doses (1, 5 or 10 mg/Kg). Macroscopic, histopathological, and immunohistochemical analyses as well as immunofluorescence experiments were performed on the oral mucosa of the animals.The samples also were used for analysis enzyme-linked immunosorbent assays and quantitative real-time polymerase chain reactions (qPCR). TELM (5 or 10 mg/kg) was able to reduce the inflammatory ulceration and infiltration in the oral mucosa of the animals, decreasing the levels of the cytokines TNF-α and IL-1β. These treatments was minimize the immunostaining for cyclooxygenase (COX)-2, matrix metalloproteinase (MMP)-9, transforming growth factor (TGF)-β, smad 2/3. The NFκB p65 and inducible nitric oxide synthase (iNOS). were reduced in the oral mucosa. Finally, TELM (10 mg/kg) increased the PPARγ gene expression and reduced STAT1 and NFκB p65 gene expression relative to the 5-FU group. Therefore, TELM prevents the OM produced by 5-FU on animal model.